2003
DOI: 10.1111/1467-7687.00306
|View full text |Cite
|
Sign up to set email alerts
|

Can dogs defy gravity? A comparison with the human infant and a non‐human primate

Abstract: We conducted four experiments with 56 adult dogs (Canis lupus familiaris) involving tasks where food was dropped through an opaque tube connected either vertically or diagonally to one of two or three goal boxes. In the first experiment, modelled after studies with children and primates, the dogs first searched significantly more often in the location directly beneath the drop-off point (a gravity bias), although this box was not connected with the tube. These results are comparable to those of human infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 17 publications
(26 reference statements)
10
72
3
1
Order By: Relevance
“…Osthaus, Slater, and Lea (2003) observed the search behavior of dogs for dropped objects and dogs' understanding of the physical mechanisms of opaque connecting tubes. Osthaus, Slater, and Lea (2003) observed the search behavior of dogs for dropped objects and dogs' understanding of the physical mechanisms of opaque connecting tubes.…”
Section: Object Learningmentioning
confidence: 99%
“…Osthaus, Slater, and Lea (2003) observed the search behavior of dogs for dropped objects and dogs' understanding of the physical mechanisms of opaque connecting tubes. Osthaus, Slater, and Lea (2003) observed the search behavior of dogs for dropped objects and dogs' understanding of the physical mechanisms of opaque connecting tubes.…”
Section: Object Learningmentioning
confidence: 99%
“…For example, several past studies successfully excluding the role of olfactory cues have demonstrated that dogs can succeed at invisible displacement problems (e.g., Triana and Pasnak 1981;Doré 1992, 1993;Watson et al 2001; but see CollierBaker et al 2004;. Additionally, dogs do show an initial gravity bias, and yet they (unlike human infants and monkeys) are able to learn to overcome their gravity bias (Osthaus et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Eszerint az alany képtelen az elvárásai alapján kialakult prepotens válasz gátlására (azaz hogy a tárgyat pontosan az elengedési pont függőleges meghosszabbításában keresse) s ez egy veleszületetten "előhúrozott" sajátossága a főemlős -és feltehetőleg más gerincesidegrendszernek is (lásd pl. Osthaus, 2003).…”
Section: Reprezentációs Vagy Végrehajtó (Executive) Képesség?unclassified